Systematic functional analysis of Leishmania protein kinases identifies regulators of differentiation or survival - N. Baker (Nature Portfolio, 2021)
Protein kinases are fundamental in cellular signalling required for Leishmania survival throughout the life cycle. Here, Baker and Catta-Preta et al. report on a kinome-wide functional study in Leishmania mexicana to define protein kinases with roles in life cycle transition.